Prayer: a transformative teaching and learning technique in project management - Ssegawa, Joseph K.; Kasule, Daniel (International Journal of Managing Projects in Business, 2015)
The purpose of this paper is to report the perceptions of students taking the Master of Project Management Programme at the University of Botswana regarding their transformative experience called “prayer”. The term “prayer” was coined because of it being the first learning activity of the lecture; and at a conceptual level, to convey reverence towards the gift of learning. “Prayer” as a learning and teaching technique involves each student identifying material containing project management concepts or issues which they present to a class of peers using any appropriate means followed by discussion and peer assessment. The material presented may be an article from a newspaper or magazine. It may be a personal documented story or a story told around a picture, artefact, poster or video relating to a project management issue. Design/methodology/approach – Students’ perceptions were obtained bymeans of a self-administered questionnaire containing open-ended questions. Content analysis was used to analyse the responses. Findings – The results of the study indicated that “prayer” provided students ingredients of transformative learning. It also proved to be a worthwhile technique for inculcating some of the graduate attributes articulated by this university and for incorporating adult learning principles. Research limitations/implications – The technique can be used to compliment traditional techniques in teaching and learning in project management training. The limitations of the results are due to the self-reporting nature of the approach and the fact that the technique has been tried on one group. Practical implications – There is a possibility that the technique can be extended to other disciplines such as business administration where students examine cases in the public domain to illustrate concepts learnt in class. Originality/value – The originality lies in its packaging of a technique the think is worth sharing among project management educators. This is because the learning activity described engages students simultaneously in research, review, presentation, and communication as well as reflection, collaborative discourse and self and peer assessment.
Keywords: Project management; Learner-centred pedagogy; Postgraduate education; Project leadership; Project training; Transformative learning